Stress Hyperglycemia As a Predictor of Adverse Outcome in Patients with Acute Ischemic Stroke: Should We Care? - Byambasukh, Oyuntugs; Gendendagva, Naranchimeg; Dagvajantsan, Byambasuren; Boldbaatar, Damdindorj (Central Asian Journal of Medical Sciences, 2022)
No abstract in English